Endoplasmic reticulum stress in bipolar disorder? – BiP and CHOP gene expression- and XBP1 splicing analysis in peripheral blood. (September 2018) - Bengesser, Susanne A.; Reininghaus, Eva Z.; Dalkner, Nina; Birner, Armin; Hohenberger, Helena; Queissner, Robert; Fellendorf, Frederike; Platzer, Martina; Pilz, Rene; Hamm, Carlo; Rieger, Alexandra; Kapfhammer, Hans-Peter; et al.
Highlights: Gene expression of Unfolded Protein Response (e.g. BIP, CHOP, XBP1 ) was analysed in Bipolar Disorder and controls. BiP gene expression was significantly higher in Bipolar Disorder. Reduced total and unspliced XPB1 levels were detected in Bipolar Disorder. XBP1 splicing itself was not altered in Bipolar Disorder. Abstract: Background: Endoplasmic Reticulum stress activates the Unfolded Protein Response, which is partially impaired in Bipolar Disorder (BD) according to previous in-vitro studies. Thus, BiP and CHOP gene expression and XBP1 splicing were analyzed in peripheral blood of study participants with BD and controls. Methods: RNA was isolated from fasting blood of study participants with BD (n = 81) and controls (n = 54) and reverse transcribed into cDNA. BiP and CHOP gene expression was analyzed with quantitative RT-PCR. Atypical splicing of XBP1 mRNA was measured by semi-quantitative RT-PCR, gel-electrophoresis and densitometry. ANCOVAs with the covariates age, BMI, sex, lithium and anticonvulsants intake were used with SPSS. Bonferroni correction was used to correct for multiple testing (adjusted p  = 0.0083). Results: BiP gene expression was significantly higher in BD than in controls ( F(1/128)  = 10.076, p  = 0.002, Partial η 2  = 0.073). Total XBP1 ( F(1/126)  = 9.550, p  = 0.002, Partial η 2  = 0.070) and unspliced XBP1 (F(1/128)= 8.803, p= 0.004, Patial η 2  = 0.065) were significantly decreased in BD. Spliced XBP1 ( F(1/126 ) = 5.848, p  = 0.017, Partial η 2  = 0.044) and the ratio spliced XBP1 / unspliced XBP1 did not differ between BD and controls ( F(1/126 ) = 0.599, p  = 0.441, Partial η 2  = 0.005). Gene expression did not differ between euthymia, depression and mania. Discussion: BiP gene expression was significantly higher in BD compared to controls. Total and unspliced XBP1 were significantly lower in BD than in the control group. Thus, both genes may be considered as putative trait markers. Nevertheless, XBP1 splicing itself did not differ between both groups.